A modified structure with asymmetric and doping barrier interlayers of GaAs-based laser diodes with both small vertical divergence angle and low threshold current. (April 2015) - Li, X.; Zhao, D.G.; Jiang, D.S.; Chen, P.; Liu, Z.S.; Shi, M.; Zhao, D.M.; Liu, W.; Zhu, J.J.; Zhang, S.M.; Yang, H.
Highlights: A modified GaAs-based LDs structure is proposed. The threshold current is investigated by numerical simulation. The vertical divergence angle of LDs is investigated by numerical simulation. A satisfactory light beam quality and a relatively low threshold current can be obtained. Abstract: The vertical divergence angle of GaAs-based laser diodes (LD) can be reduced by usually increasing waveguide thickness and inserting low index layers between waveguide layers and cladding layers, but it will also induce an increase of the threshold current. It is proposed to make the inserted low index interlayers doped and asymmetric to simultaneously reduce vertical divergence angle and alleviate the deterioration of threshold current. The simulation results indicate that the carrier leakage and injection are improved due to the change of energy band profile. The characteristics of newly designed laser structure indicate a satisfactory light beam quality and a relatively low threshold current density.